Genetic variants in the SHISA6 gene are associated with delayed cognitive impairment in two family datasets. Issue 2 (1st May 2022) - Ramos, Jairo; Caywood, Laura J.; Prough, Michael B.; Clouse, Jason E.; Herington, Sharlene D.; Slifer, Susan H.; Fuzzell, M. Denise; Fuzzell, Sarada L.; Hochstetler, Sherri D.; Miskimen, Kristy L.; Main, Leighanne R.; Osterman, Michael D.; et al.
Abstract: Introduction: Studies of cognitive impairment (CI) in Amish communities have identified sibships containing CI and cognitively unimpaired (CU) individuals. We hypothesize that CU individuals may carry protective alleles delaying age at onset (AAO) of CI. Methods: A total of 1522 individuals screened for CI were genotyped. The outcome studied was AAO for CI individuals or age at last normal exam for CU individuals. Cox mixed‐effects models examined association between age and single nucleotide variants (SNVs). Results: Three SNVs were significantly associated ( P < 5 × 10 –8 ) with AAO on chromosomes 6 (rs14538074; hazard ratio [HR] = 3.35), 9 (rs534551495; HR = 2.82), and 17 (rs146729640; HR = 6.38). The chromosome 17 association was replicated in the independent National Institute on Aging Genetics Initiative for Late‐Onset Alzheimer's Disease dataset. Discussion: The replicated genome‐wide significant association with AAO on chromosome 17 is located in the SHISA6 gene, which is involved in post‐synaptic transmission in the hippocampus and is a biologically plausible candidate gene for Alzheimer's disease.